SPECTRAL MEMORIES: AESTHETIC RESPONSES TO THE FINANCIAL CRASH IN ICELAND 2008 - Knútsdóttir, Vera (The Nordic Journal of Aesthetics, 2020)
In October 2008, one of the largest bank crashes in history struck Iceland, a country of three hundred and thirty five thousand inhab-itants. The aim of the article is to examine two cultural responses to the crash and the crisis that followed. More precisely, the aim is to analyse how the creation of the haunted house in I Remember You, a crash-horror story by crime writer Yrsa Sigurðardóttir, as well as the spectral half-built houses portrayed by visual artist Guðjón Ketilsson refer quite directly, yet spectrally, to the period. The spec-tral themes of the two works give the opportunity to discuss the moment following the crash as a moment of haunting—but who is haunted and by whom?